2022
DOI: 10.1007/s10518-022-01329-8
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of 5G-based architecture supporting data-driven digital twins updating and matching in seismic monitoring

Abstract: Digital Twins (DT) models are gaining special attention in the management and maintenance of facilities. The quality of data contained in these models may be enhanced by the use of processed information coming from long-term Structural Health Monitoring (SHM). In this case real time processing and updating in systems using sensor networks for SHM need low latency and reliable communication. This paper presents a solution for exploiting DT models for SHM and early warning solutions improvement. The case study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…These models were deemed appropriate for the present study due to their common characteristics. Firstly, they have been successful in data-driven structural health-monitoring [63][64][65][66][67] and investigating infrastructure problems in previous studies [28,33,68,69]. Secondly, the existing studies have demonstrated the effectiveness of Random Forest [70,71], XGboost [22,28], and ANN [25,29,33,72,73] in capturing the complex and nonlinear relationships among the variables involved in predicting bridge condition rating.…”
Section: Results Of Training and Evaluating Modelsmentioning
confidence: 99%
“…These models were deemed appropriate for the present study due to their common characteristics. Firstly, they have been successful in data-driven structural health-monitoring [63][64][65][66][67] and investigating infrastructure problems in previous studies [28,33,68,69]. Secondly, the existing studies have demonstrated the effectiveness of Random Forest [70,71], XGboost [22,28], and ANN [25,29,33,72,73] in capturing the complex and nonlinear relationships among the variables involved in predicting bridge condition rating.…”
Section: Results Of Training and Evaluating Modelsmentioning
confidence: 99%
“…More efficient programming languages were identified to present the system using a micro-service architecture. Additionally, issues identified during the testing phase of prior system implementations were resolved [ 37 ].…”
Section: Description Of the Smart-wired Monitoring Systemmentioning
confidence: 99%
“…Because DT integrates artificial intelligence methods such as support vector machines and neural networks, it is highly accurate in predicting fire scale, flood degree, and hurricane trajectory [129][130][131]. At the same time, with the maturity of the Internet of Things technology, DT can quickly and accurately share the disaster situation and issue early warnings of the crisis to people who may be affected by the disaster [132].…”
Section: Mitigationmentioning
confidence: 99%